Culture and Diagnosis of MCI in Hispanics: A Literature Review. (30th August 2019) - Briceño, E; Mehdipanah, R; Gonzales, X; Langa, K; Levine, D; Garcia, N; Longoria, R; Giordani, B; Heeringa, S; Morgenstern, L
Abstract: Objective: Hispanics are a rapidly growing and aging segment of the US population. There is a critical need to accurately and efficiently detect those at risk for dementia, particularly those with Mild Cognitive Impairment (MCI). MCI diagnosis typically relies on neuropsychological tests, although cultural and linguistic factors impact neuropsychological test scores. The current study reviews neuropsychological studies on MCI in Hispanics to evaluate the factors in testing for MCI diagnosis. Participants and Method: Studies were identified from a literature search utilizing Web of Science, PubMed, Google Scholar, and Scopus, using search terms "Hispanic OR Mexican American" and "Mild Cognitive Impairment, " and from the reference sections of studies identified through this search. Studies utilizing neuropsychological tests in the diagnosis of MCI for Hispanics living in the US were identified and reviewed. Approaches for sample characterization (e.g., country of origin and of education, literacy, language preference and proficiency), neuropsychological test methods (e.g., test selection and translation, normative data source), and method of MCI diagnosis were reviewed. Results: Considerable variability was found across studies with regard to the incorporation – and the method of incorporation – of cultural factors and their consideration in the MCI diagnosis process for Hispanics. For example, several studies did not report their sample's country of education, source of normative data used for determination of cognitive impairment, or method of test adaptation/translation. Conclusions: Diagnosis of MCI in Hispanics has been complicated by a dearth of culturally appropriate neuropsychological assessment tools and normative data, which likely contributes to inconsistency across studies. Future studies are needed to further develop culturally appropriate neuropsychological methods to evaluate MCI in Hispanics in the US and to improve diagnostic accuracy in this population.